(untitled) (Revista Brasileira Multidisciplinar, 2009)
This paper examines the potential of Physical Education discipline in the process of school inclusion of students from the lower working classes in a peripherical elementary school EMEF Ricardo C. C. Monteiro, popularly known as CAIC Vale do Sol, because of its location in the section of the city of Araraquara, SP, named as Vale do Sol ( Sun Valley). The data, obtained from interviews with people of the institution, confirmed the importance of the discipline Physical Education and of the Project SEMEAR as strategies for maintaining the continuity of the students’ presence at school and the positive consequences of this inclusion. Considering the sociological character of this research, the studies of Pierre Bourdieu and followers offered the categories of sociological analysis which ensured the necessary support to verify the restructuring of the primary habitus of the students acquired in their families in a habitus cultivated in school, to assure the acceptance of symbolic codes imposed by the educational institution and legitimized by society. We can conclude that Physical Education as a compulsory subject in school curriculum plays a key role in this educational institution and especially to those families belonging to this class fraction that consciously or unconsciously ascribe to it (Physical Education) the continuity of the school trajectory of their children, making possible a better quality of life.